ENSAIO DE VERMÃFUGOS EMPREGADOS EM EQUINOS - Amaral, DÃ©o Carlos Cliquet do; Zamith, Adiel Paes Leme; Vencovsky, Rolando; Bunning, Bernhard (REVISTA DE AGRICULTURA, 2015)
ENSAIO DE VERMÃFUGOS EMPREGADOS EM EQUINOS